(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The social order, which always needs to flow smoothly or unhindered, is unaffected by any issues that society creates on its own or for its own self-serving ends. When the social order reaches a point of stagnancy, its degrading effects can be clearly seen in the cataclysm of disturbed law and order.The majority of individuals in our culture have always been in favour of women's empowerment. In terms of legislation that benefits them, women currently hold the upper hand. Things have changed in society from the period when women were marginalized and seen to be weak to the present, when women are respected and not all that weak. Prior to 1983, there was no particular legislative provision addressing domestic abuse against women. Husbands who abuse their wives may be found guilty under general statutes relating to homicide, injury, aiding suicide, or wrongful detention.The Protection of Women from Domestic Violence Act, a civil law passed in 2005, aims to provide relief to the party who has been wronged—in this case, the woman who experiences domestic violence. The Constitution of India's Article 15 (2), which specifies that "State might make specific measures for women and children" in order to realize the right to equality, is the source of the Act. This Act represented the first significant attempt to rewrite the law within an established structure. This article shows the Critical Analysis of Misuse of Domestic Violence Act 2005.